Biological control of the larger grain borer - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
A predatory beetle from Costa Rica could soon be released in Togo to control the larger grain borer. In semi-field trials the beetle Teretriosoma nigrescens reduced larger grain borer populations by 70% in just over three months. In 1984 the German...